Republic of Poland : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Poland. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2022)
The Polish economy has rebounded strongly, with policy actions limiting the damage from the pandemic-induced recession by supporting employment and avoiding unnecessary bankruptcies. While the pandemic continues to take a toll on lives, the economy has been less impacted by successive waves of the pandemic.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; United Kingdom